PENGARUH HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP MINAT BELI KONSUMEN PADA TOKO PAKAIAN NANIKE COLLECTION DI KABUPATEN JEMBER - Firmansyah, Rama; Hermawan, Haris; Diansari, Tatit (Fakultas Ekonomi dan Bisnis, 2023)
The fashion business is a business that is in great demand because it has big prospects. Currently, the fashion industry is emerging with attractive fashion designs which are becoming a trend among Generation Z. By improving product quality and a good brand image, buying interest will arise and consumers will make repeat purchases because it meets their expectations. This research aims to test and analyze the influence of price, product quality and brand image on consumer purchasing interest at the Nanike Collection clothing store in Jember district. This type of research is quantitative. The population in this research is consumers of the Nanike Collection clothing store. The sample used was 160 respondents. The analysis tool uses multiple linear regression. The research results prove that price, product quality and brand image have a significant effect on consumer buying interest at the Nanike Collection clothing store, Jember Regency.